Are financial reports useful? The views of New Zealand public versus private users - Ehalaiye D; Laswad F; Botica Redmayne N; Stent W; Cai L (John Wiley and Sons, Inc on behalf of CPA Australia)
This study reports on surveys conducted with users of financial reports in New Zealand. We compare findings for users of reports of two types of for-profit entities, namely those with public accountability (public entities) and those with no public accountability (private entities). The findings indicate that both types of users have similar perceptions regarding the usefulness of financial statements, with the income statement and balance sheet rated as the most useful components. Furthermore, both types of users, especially private users, perceive financial statements as the most important information source for decision making. Public users have a greater interest in supplementary information than private users. The findings of this study contribute to the debate around differential reporting for private companies and have policy implications with regard to the user-needs approach to accounting standard setting.
This is the pre-peer reviewed version of the following article: "Are Financial Reports Useful? The Views of New Zealand Public Versus Private Users", which has been published in final form at https://doi.org/10.1111/auar.12254 . This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Use of Self-Archived Versions.
Keywords: 1499 Other Economics; 1501 Accounting, Auditing and Accountability